PENGARUH KESADARAN ETIS TERHADAP KOMITMEN PROFESI AKUNTAN DI KOTA MAKASSAR - Rukmana, Risa; Saleh, Andi Mulia; Sarinah, Sarinah (Universitas Patria Artha, 2022)
The purpose of this study is to analyze the influence of ethical awareness on the commitment of the accounting profession. The population used in this study were public accountants in Makassar City. The type of data used in this research is quantitative data. Sources of data used are primary data, data obtained by distributing questionnaires. The method of analysis used linear regression analysis. The previous data were tested by instruments with the classical assumption test first. The results of the study indicate that Ethical Awareness has an effect on the commitment of the accounting profession.